2009
DOI: 10.1136/bmj.b4347
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of self reported smoking status by pregnant women for estimating smoking prevalence: a retrospective, cross sectional study

Abstract: Objective To determine what impact reliance on self reported smoking status during pregnancy has on both the accuracy of smoking prevalence figures and access to smoking cessation services for pregnant women in Scotland. Design Retrospective, cross sectional study of cotinine measurements in stored blood samples. Participants Random sample (n=3475) of the 21029 pregnant women in the West of Scotland who opted for second trimester prenatal screening over a one year period. Main outcome measure Smoking status va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
281
4
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(302 citation statements)
references
References 28 publications
10
281
4
7
Order By: Relevance
“…This study has shown that linked data differentially increased the ascertainment of smokers, not only in women who are at higher risk of adverse outcomes (older age, multi-fetus pregnancy, diabetes, hypertension) but also in women who are known to underreport their smoking status (older age, married, immigrants from non-English speaking countries, and high socioeconomic status). 23,26,27 Factors contributing to voluntary disclosure of smoking among 51 In addition, it is also important that linking the records has resulted in a greater detection of smokers among women who gave birth in private and rural hospitals, given existing evidence that the data recording in these hospitals is less likely to be complete than in public or urban hospitals. 17,52 Comparing the two enhanced algorithms, it was found that additional information from antenatal admissions provided little enhanced benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that linked data differentially increased the ascertainment of smokers, not only in women who are at higher risk of adverse outcomes (older age, multi-fetus pregnancy, diabetes, hypertension) but also in women who are known to underreport their smoking status (older age, married, immigrants from non-English speaking countries, and high socioeconomic status). 23,26,27 Factors contributing to voluntary disclosure of smoking among 51 In addition, it is also important that linking the records has resulted in a greater detection of smokers among women who gave birth in private and rural hospitals, given existing evidence that the data recording in these hospitals is less likely to be complete than in public or urban hospitals. 17,52 Comparing the two enhanced algorithms, it was found that additional information from antenatal admissions provided little enhanced benefit.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Studies conducted in Australia and elsewhere using biochemical testing to validate self-reporting of smoking status have reported that between 6% and 39% of smoking women do not disclose their smoking status. [27][28][29][30][31] Greater levels of non-disclosure are found in women who are older, married and have higher socioeconomic status. 23,26,27 As a result, the true prevalence of maternal smoking is likely to be under-estimated and opportunities for smoking cessation interventions could be missed.…”
mentioning
confidence: 99%
“…Parents were encouraged to consult their "maternity passes" when answering the questions on gestational age and weight at birth. Recall of smoking habits has been reported to yield valid results in general (42), but the validity of self-reported smoking in pregnancy -which was also the standard method of smoking assessment in other studies (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) -is doubtful, since the number of smoking mothers might be underestimated (43). However, we do not feel that this limitation should have caused substantial bias to the main results of our study: If a number of mothers who smoked during pregnancy were misclassified as non-smokers, the effect size of smoking on BMI-SDS might even have been underestimated in the overall analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in inaccurate data and an overestimation of the quit rate. 22 We did not explore why the 1-800 Quit line was so underused. Possible factors could include lack of readiness/motivation to quit after discharge and the requirement for the patient to be proactive in contacting the Quit line rather than vice versa.…”
Section: Discussionmentioning
confidence: 99%